The Influence of Authentic Leadership on Employee Performance through Employee Engagement at the Public Drinking Water Company Tirta Kanjuruan Malang Regency - Ivan Widjaja; Dewi Yustiana; Koen Irianto Uripan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyse the effect of authentic leadership on employee performance with employee engagement as a mediating variable at the Regional Drinking Water Company (PERUMDA) Tirta Kanjuruhan, Malang Regency. Authentic leadership is a leadership style that emphasises transparency, ethics, and honest relationships between leaders and employees, which is believed to increase employee engagement and performance. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees of PERUMDA Tirta Kanjuruhan and analysed using Partial Least SquaresStructural Equation Modeling (PLS-SEM) technique. The results showed that authentic leadership has a positive and significant effect on employee engagement and employee performance. In addition, employee engagement was shown to act as a mediating variable that strengthens the relationship between authentic leadership and employee performance. The findings confirm the importance of authentic leadership in creating a work environment that supports employee engagement, which ultimately improves individual and organisational performance. This study provides implications for company management in developing more effective leadership strategies to improve employee productivity and well-being.